A method for producing lithium-based ceramic particles using a lithium-containing molten compound and lithium-based ceramic particles
Patent Information
- Application Number
- CN202510822756.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-19
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2045-06-19
AI Technical Summary
[0002]现在大多数商用锂离子电池均采用有机电解液,不仅存在易燃易爆的安全问题,而且会造成高污染、高排放和温室效应等环境问题,这导致需要迫切找到一种替代其的安全性的电池,目前的解决方式是将液态电解液替换为固态电解质来降低安全隐患,这种电池被叫做固态锂离子电池,在众多固体电解质中,以石榴石结构的LLZO为代表的锂基陶瓷因为电导率高和电化学稳定性好等优点而倍受关注
[0047]与现有技术相比,本申请的有益效果至少在于:
Smart Images

Figure CN120535310B_ABST
Abstract
Description
Technical Field
[0001] This application belongs to the field of lithium-based ceramic generation technology, specifically relating to a method for preparing lithium-based ceramic particles using lithium-containing molten compounds and the lithium-based ceramic particles themselves. Background Technology
[0002] Currently, most commercially available lithium-ion batteries use organic electrolytes, which not only pose safety risks due to flammability and explosion, but also cause environmental problems such as high pollution, high emissions, and the greenhouse effect. This necessitates finding a safer alternative battery. The current solution is to replace liquid electrolytes with solid electrolytes to reduce safety hazards; such batteries are called solid-state lithium-ion batteries. Among various solid electrolytes, lithium-based ceramics, represented by garnet-structured LLZO, have attracted much attention due to their high conductivity and good electrochemical stability. The phase structure, purity, and morphology of lithium-based ceramic particles have a significant impact on their properties; therefore, a method for preparing lithium-based ceramic particles with good phase structure and high purity is needed. Summary of the Invention
[0003] In view of this, this application provides a method and application for preparing lithium-based ceramic particles using lithium-containing molten compounds. The lithium-based ceramic particles obtained by this method have good phase structure, high purity, and good morphology (sphericity).
[0004] In a first aspect, this application provides a method for preparing lithium-based ceramic particles using a lithium-containing molten compound, comprising the following steps:
[0005] Step S1: Provide raw material powder according to the stoichiometric ratio of lithium-based ceramics, and obtain lithium-based ceramic pre-fired powder after pre-firing;
[0006] Step S2: The lithium-based ceramic pre-sintered powder is mixed with a lithium-containing molten compound and then sintered. The lithium-containing molten compound is in a molten state, and the lithium-based ceramic pre-sintered powder is sintered in this environment to obtain a sintered product.
[0007] Step S3: After cooling the sintered product, wash it with a solvent to dissolve and remove the lithium-containing molten compound in the sintered product, so as to obtain lithium-based ceramic particles.
[0008] Based on this application, lithium-based ceramic pre-sintered powder is mixed with a lithium-containing molten compound and then directly sintered. The lithium-containing molten compound is in a molten state during sintering and has a certain solubility for each component in the lithium-based ceramic pre-sintered powder. The metal sources in the lithium-based ceramic pre-sintered powder can undergo atomic-level mass exchange reactions in the molten liquid phase. Therefore, compared to general solid-phase sintering reactions, this method is a solid-liquid reaction, which can significantly increase the sintering rate. Simultaneously, the lithium-based ceramic body obtained by sintering in the liquid phase has a more uniform chemical element composition and lower impurity content. Therefore, the lithium-based ceramic body has a good phase structure, high phase purity, and fewer impurities. The better the phase structure, the higher the purity and the fewer crystal defects. On the other hand, using a lithium-containing molten compound can further compensate for the volatilization of lithium in the lithium-based ceramic pre-sintered powder during the sintering process without introducing new impurity elements, thereby further improving the phase purity of the lithium-based ceramic body. Therefore, the lithium-based ceramic particles prepared by this method have high phase purity.
[0009] It should also be noted that, compared to solid-state sintering reactions in related technologies, which generally require granulation and pressing of the lithium-based ceramic powder before sintering to ensure sufficient reaction of the components in the pre-sintered lithium-based ceramic powder to obtain the lithium-based ceramic body, allowing the components to mix and come into contact to facilitate mass exchange, the method provided in this application uses a molten lithium-containing compound as the reaction medium. Therefore, granulation and pressing are unnecessary. During sintering, the components in the pre-sintered lithium-based ceramic powder can undergo atomic-level mass exchange in the molten lithium-containing compound, resulting in lithium-based ceramic particles with a more uniform chemical composition, thus exhibiting better phase structure and purity. Furthermore, compared to solid-state sintering reactions, this method simplifies the process and shortens the sintering time due to the omission of certain steps and the faster reaction rate in the liquid phase, thereby effectively reducing production costs.
[0010] In some embodiments, the lithium-containing molten compound includes at least one of lithium carbonate, lithium nitrate, lithium chloride, lithium oxide, and lithium hydroxide. Based on the above embodiments, these compounds have relatively low melting points and do not introduce new impurity ions into the reaction system. They are also easily removed from the calcined product by washing, resulting in low separation costs.
[0011] In some embodiments, the lithium-containing molten compound includes lithium carbonate. Based on the above embodiments, during the sintering process, lithium carbonate decomposes to produce carbon dioxide. The generated gas can prevent the agglomeration of lithium-based ceramic grains, thereby making the particle size of the lithium-based ceramic particles easier to control and resulting in a more uniform distribution.
[0012] In some embodiments, in step S2, the mass ratio of the lithium-based ceramic pre-calcined powder to the lithium-containing molten compound is 1:1 to 8.
[0013] In some of the above embodiments, when the mass ratio of lithium-based ceramic pre-sintered powder to lithium-containing molten compound meets the above conditions, the sphericity of the lithium-based ceramic particles is better, the particle size of the lithium-based ceramic particles is easier to control, and lithium-based ceramic particles of different sizes can be obtained by adjusting the sintering time. For example, the mass ratio of the lithium-based ceramic pre-sintered powder to the lithium-containing molten compound can be 1:1, 1:1.5, 1:2, 1:2.5, 1:3, 1:3.5, 1:4, 1:4.5, 1:5, 1:5.5, 1:6, 1:6.5, 1:7, 1:7.5, 1:8, or any of the above values.
[0014] In some embodiments, in step S2, the mass ratio of the lithium-based ceramic pre-sintered powder to the lithium-containing molten compound is 1:3 to 5. Based on the above embodiments, when the mass ratio of the lithium-based ceramic pre-sintered powder to the lithium-containing molten compound meets the above conditions, the particle size distribution of the lithium-based ceramic particles is more uniform, which is more conducive to obtaining lithium-based ceramic particles with uniform particle size.
[0015] In some embodiments, the sintering conditions in step S2 include: a sintering temperature of 900–1200°C and a sintering time of 12–48 h.
[0016] Based on the above embodiments, under the above conditions, the sintered lithium-based ceramic particles have good sphericity, and the particle size of the lithium-based ceramic particles gradually increases with the increase of sintering time. Different sintering times can be controlled within this range to obtain lithium-based ceramic particles of different particle sizes.
[0017] In some embodiments, the sintering time is 12–14 h. During this time, the volume average particle size Dv50 of the lithium-based ceramic particles is 10–22 μm.
[0018] In some embodiments, the sintering time is 14–16 h. During this time, the volume average particle size (Dv50) of the lithium-based ceramic particles is 18–42 μm.
[0019] In some embodiments, the sintering time is 16–20 h. During this time, the volume average particle size (Dv50) of the lithium-based ceramic particles is 38–62 μm.
[0020] In some embodiments, the sintering time is 20–24 h. During this time, the volume average particle size (Dv50) of the lithium-based ceramic particles is 58–82 μm.
[0021] In some embodiments, the sintering time is 24–48 h. During this time, the volume average particle size (Dv50) of the lithium-based ceramic particles is 78–110 μm.
[0022] In this process, when sintering with lithium-containing molten compounds (i.e., sintering using molten salt method), the particle size of lithium-based ceramic particles can be highly controllable by controlling the sintering time.
[0023] In this application, sintering time is sometimes also referred to as holding time.
[0024] In some embodiments, the lithium-based ceramic is selected from any of the substances shown in Formula 1;
[0025] Li 7-x La3Zr 2-x M x O 12 Formula 1
[0026] Where M is a doping element, and M is selected from at least one of Ta, Nb, W, and Ti; the value range of x is: 0≤x≤1.0.
[0027] In some of the above embodiments, the lithium-based ceramic satisfying Formula 1 is an LLZO-based solid electrolyte, which has high ionic conductivity and stable structure and strength, and can be used as a solid electrolyte in batteries; at the same time, by doping M element in Zr sites, the LLZO-based solid electrolyte can maintain a cubic phase at room temperature, which has higher ionic conductivity than the tetragonal phase of the LLZO-based solid electrolyte.
[0028] In some embodiments, the raw materials also include a La source, a Zr source, and a dopant element M source.
[0029] In some embodiments, the Li source includes at least one of lithium carbonate, lithium nitrate, and lithium hydroxide, preferably lithium carbonate.
[0030] In some embodiments, the La source includes at least one of lanthanum oxide, lanthanum hydroxide, and lanthanum nitrate, preferably lanthanum hydroxide.
[0031] In some embodiments, the Zr source includes at least one of zirconium oxide, zirconium hydroxide, and zirconium nitrate, preferably zirconium oxide.
[0032] In some embodiments, the dopant element M source is a Ta source, which includes one of tantalum oxide, tantalum hydroxide, and tantalum nitrate, preferably tantalum oxide.
[0033] In some embodiments, the pre-firing conditions in step S1 include: pre-firing at 800–1000°C for 10–24 hours. Based on the above embodiments, the lithium-based ceramic pre-fired powder obtained under these conditions has good sintering activity, which is more conducive to obtaining lithium-based ceramic particles with high phase purity.
[0034] In some embodiments, in step S1, the raw material powder includes lithium salt, the mass of lithium element in the lithium source is denoted as m, and the theoretical amount of lithium element is denoted as m0, satisfying 1.1×m0≤m≤1.2×m0. Based on the above embodiments, an appropriate excess of lithium element can compensate for the volatilization of lithium element during the pre-firing process, improve the sintering activity of lithium-based ceramic pre-fired powder, and obtain lithium-based ceramic particles with better performance.
[0035] In some embodiments, in step S3, the solvent includes water and / or ethanol.
[0036] It is understandable that the role of the solvent is to dissolve the lithium-containing molten compounds in the sintered product. Therefore, the solvent can be selected based on the type of lithium-containing molten compound and its good solubility.
[0037] In some embodiments, step S3 further includes: after washing, drying the washed sintered product and then grinding it to obtain lithium-based ceramic particles.
[0038] Secondly, this application provides lithium-based ceramic particles prepared according to the method described in any embodiment of the first aspect.
[0039] Based on this application, since the lithium-based ceramic particles are prepared according to the method described in any embodiment of the first aspect, they have the beneficial effects of the first aspect, namely, they have good phase structure, high purity, fewer impurities, high sphericity and uniform particle size distribution.
[0040] In some embodiments, the volume average particle size Dv50 of the lithium-based ceramic particles is 10–110 μm. Based on the above embodiments, when the volume average particle size Dv50 of the lithium-based ceramic particles is 10–110 μm, it has good sphericity, as obtained through the first aspect of the embodiments.
[0041] In some embodiments, the volume average particle size Dv50 of the lithium-based ceramic particles is 10–22 μm.
[0042] In some embodiments, the volume average particle size Dv50 of the lithium-based ceramic particles is 18–42 μm.
[0043] In some embodiments, the volume average particle size Dv50 of the lithium-based ceramic particles is 38–62 μm.
[0044] In some embodiments, the volume average particle size Dv50 of the lithium-based ceramic particles is 58–82 μm.
[0045] In some embodiments, the volume average particle size Dv50 of the lithium-based ceramic particles is 78–110 μm.
[0046] Using the method described in the first aspect, lithium-based ceramic particles with different particle sizes can be obtained to meet different application requirements and expand the scope of applications.
[0047] Compared with the prior art, the beneficial effects of this application are at least as follows:
[0048] 1. This method directly uses a lithium-containing molten compound as the reaction medium. The reactants have a certain solubility in the lithium-containing molten compound. Utilizing the solubility of the reactants in the molten compound, the reactants can be rapidly and uniformly distributed, allowing the reaction to proceed at the atomic level. After the reaction is completed, a suitable solvent is used to dissolve the lithium-containing molten compound. After filtration and washing, the synthesized product is obtained. This method greatly accelerates the diffusion rate of ions, enabling the reactants to achieve atomic-scale mixing in the liquid phase. The reaction is transformed from a solid-solid reaction to a solid-liquid reaction. Compared with the conventional solid-phase method, it has advantages such as simple process, low synthesis temperature, short holding time, uniform chemical composition of the synthesized powder, good particle morphology, high phase purity, and uniform distribution.
[0049] 2. This method allows for the preparation of lithium-based ceramic particles of various sizes by adjusting the sintering time. Attached Figure Description
[0050] Figure 1 The XRD pattern of the LLZTO particles in Example 1 of this application;
[0051] Figure 2 This is a scanning electron microscope image of the LLZTO particles in Example 1 of this application. Detailed Implementation
[0052] To make the objectives, technical solutions, and advantages of this application clearer, the following detailed description is provided in conjunction with embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the scope of this application.
[0053] In the description of this specification, the references to terms such as "one embodiment," "some embodiments," "illustrative embodiment," "example," "specific example," or "some examples," etc., indicate that a specific feature, structure, material, or characteristic described in connection with an embodiment or example is included in at least one embodiment or example of this application. In this specification, the illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.
[0054] Furthermore, the terms "first" and "second" are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Thus, a feature defined as "first" or "second" may explicitly or implicitly include at least one of that feature. In the description of this application, "multiple" means at least two, such as two, three, etc., unless otherwise explicitly specified.
[0055] Currently, there are two main methods for synthesizing lithium-based ceramics: the conventional solid-state method and the wet chemical method. The conventional solid-state method uses solid oxides of each component as raw materials, dispersed in an insoluble organic solvent. The raw materials are then thoroughly refined and mixed using mechanical abrasive methods such as ball milling to obtain a slurry. After drying, it is calcined at high temperature to form the phase. This method has some drawbacks, such as high energy consumption, low efficiency, insufficiently fine powder, and susceptibility to impurities. The wet chemical method generally uses soluble salts of each component, dispersed in water or a soluble organic solvent. Extremely fine precursor particles are obtained through processes such as sol-gel coagulation or combustion. Generally, the phase-formed powder obtained by the wet chemical method has good crystallinity, fine particle size, and high activity, which can effectively reduce the subsequent sintering temperature. In other types of ceramics, the wet chemical method often improves the quality of the finished ceramic product. However, according to the literature review, the quality of ceramics obtained by the wet chemical method in lithium-based ceramic systems is not high. This may be related to the structure of the lithium-based ceramic body itself and the presence of Li element.
[0056] This invention proposes a method for preparing lithium-based ceramic particles using lithium-containing molten compounds. The method employs one or more lithium-containing molten compounds as the reaction medium. The reactants have a certain solubility in the molten lithium-containing compound, allowing the reaction to occur at the atomic level. After the reaction, the lithium-containing molten compound is dissolved in a suitable solvent, and the synthesized product is obtained after filtration and washing. This method significantly accelerates the diffusion rate of ions and particles, enabling atomic-scale mixing of reactants in the liquid phase. The reaction is thus transformed from a solid-solid reaction to a solid-liquid reaction. Compared to conventional solid-phase methods, this method offers advantages such as simple process, low synthesis temperature, short holding time, uniform chemical composition of the synthesized powder, good crystal structure, good particle morphology, and high phase purity. Therefore, the technical solution of this application will contribute to the development and application of solid-state lithium-ion batteries.
[0057] Based on the proposed solution to the technical problem, a method for preparing lithium-based ceramic particles using lithium-containing molten compounds is described below. The preparation of LLZTO particles (using Ta-doped LLZO-based ceramics) is used as an example. This method is intended to be implemented through the following means:
[0058] Firstly, this technical solution requires the use of LLZTO pre-calcined powder prepared at 900℃~1200℃;
[0059] ① Weigh the prepared LLZTO pre-calcined powder, add a certain amount of lithium-containing molten compound and mix evenly. Grind the mixture and sinter it at 900℃~1200℃ for a certain time (12~48h). Let it cool naturally to room temperature, take out the product, and wash it with deionized water until the solution is clear to remove excess salt from the surface of the product.
[0060] ② Dry the product from step ① in an oven at 50℃~100℃. After drying, grind the powder to obtain the final product LLZTO.
[0061] Under the condition that the mass ratio of pre-calcined powder to lithium-containing molten compound is 1:1 to 8 in the above steps, LLZTO particles with controllable grain size are prepared by different holding times (holding time of 12 to 14 h yields a particle size D50 of 10 to 22 μm; holding time of 14 to 16 h yields a particle size D50 of 18 to 42 μm; holding time of 16 to 20 h yields a particle size D50 of 38 to 62 μm; holding time of 20 to 24 h yields a particle size D50 of 58 to 82 μm; holding time of 24 to 48 h yields a particle size D50 of 78 to 110 μm).
[0062] Optionally, the mass ratio of pre-burned powder to lithium-containing molten compound is 1:1 to 8.
[0063] Optionally, the upper limit of the mass ratio of pre-burned powder to lithium-containing molten compound is selected from any one of 1:1, 1:2, 1:3, 1:4, 1:5, and 1:6, and the lower limit of the mass ratio of pre-burned powder to lithium-containing molten compound is selected from any one of 1:2, 1:3, 1:4, 1:5, 1:6, and 1:8.
[0064] Optionally, the mass ratio of pre-burned powder to lithium-containing molten compound is preferably 1:3 to 5.
[0065] Optionally, the sintering time is preferably 12 to 48 hours.
[0066] Optionally, the lithium-containing molten compound is preferably Li2CO3, LiNO3, LiCl, Li2CO3+LiNO3, Li2CO3+Li2O, LiNO3+LiOH, or LiNO3+LiCl.
[0067] More preferably, the lithium-containing molten compound is lithium carbonate, which decomposes into carbon dioxide and lithium oxide at high temperature. The carbon dioxide gas affects the growth of the grains and can prevent the LLZTO grains from agglomerating at high temperature, resulting in appropriate grain size and uniform distribution.
[0068] Optionally, the pre-calcined powder can be obtained by sintering lithium carbonate, zirconium oxide, lanthanum oxide, and tantalum oxide at 800–1000 °C for 10–24 h.
[0069] The solution of this application will be described below with reference to the following specific embodiments. Unless otherwise specified, the raw materials used in the following embodiments are all from commercially available products, and the devices or equipment used are all purchased from conventional market sales channels.
[0070] Preparation of LLZTO pre-calcined powder:
[0071] Ta₂O₅, Li₂CO₃, La₂O₃, ZrO₂ according to Li 6.4 La3Zr 1.4 Ta 0.6 O 12 The materials were mixed according to the metering ratio, with Li2CO3 in excess by 18%. After mixing, the mixture was placed in a ball mill at a ratio of ball:material:water = 2:1:1, and the milling speed was 500 rpm for 5 hours. After milling, the mixture was dried and crushed. The crushed powder was placed in an Al2O3 crucible and pre-calcined at 920℃ for 720 min to obtain pre-calcined powder.
[0072] Example 1
[0073] The preparation of LLZTO particles includes the following steps:
[0074] Weigh LLZTO pre-calcined powder and Li2CO3 at a mass ratio of 1:4, pour the mixed powder into a mortar and grind thoroughly for 30 minutes to ensure uniform mixing. Place the uniformly ground powder into an alumina crucible, set the muffle furnace temperature to 1100℃ at a rate of 5℃ / min, and maintain the temperature in the furnace for 12 hours. After cooling to room temperature, remove the sample and ultrasonically clean it with deionized water until the supernatant is clear. Place the ultrasonically cleaned sample in a drying oven and dry it at 60℃. After drying, LLZTO particles with good morphology and uniform particle distribution are obtained, and the volume average particle size Dv50 is measured to be 18μm.
[0075] The LLZTO particles obtained in Example 1 were subjected to XRD and scanning electron microscopy tests, respectively. The XRD patterns are shown below. Figure 1 As shown, the product is LLZTO with a garnet structure, exhibiting good phase structure, high purity, and few impurities; the scanning electron microscope image is shown below. Figure 2 As shown, the obtained product has good particle morphology, no adhesion or agglomeration, and is evenly distributed.
[0076] Example 2
[0077] The preparation of LLZTO particles includes the following steps:
[0078] Weigh LLZTO pre-calcined powder and LiOH at a mass ratio of 1:2, pour the mixed powder into a mortar and grind thoroughly for 30 minutes to ensure uniform mixing. Place the uniformly ground powder into an alumina crucible, set the muffle furnace temperature to 1200℃ at a rate of 5℃ / min, and maintain the temperature in the furnace for 15 hours. After cooling to room temperature, remove the sample and ultrasonically clean it with deionized water until the supernatant is clear. Place the ultrasonically cleaned sample in a drying oven and dry it at 60℃. After drying, LLZTO particles with good morphology are obtained, and the volume average particle size Dv50 is measured to be 30μm.
[0079] Example 3
[0080] The preparation of LLZTO particles includes the following steps:
[0081] Weigh LLZTO pre-calcined powder and LiCl at a mass ratio of 1:1, pour the mixed powder into a mortar and grind thoroughly for 30 minutes to ensure uniform mixing. Place the uniformly ground powder into an alumina crucible, set the muffle furnace temperature to 900℃ at a rate of 5℃ / min, and maintain the temperature in the furnace for 18 hours. After cooling to room temperature, remove the sample and ultrasonically clean it with deionized water until the supernatant is clear. Place the ultrasonically cleaned sample in a drying oven and dry it at 60℃. After drying, LLZTO particles with good morphology are obtained, and the volume average particle size Dv50 is measured to be 50μm.
[0082] Example 4
[0083] The preparation of LLZTO particles includes the following steps:
[0084] Weigh LLZTO pre-calcined powder and LiNO3 at a mass ratio of 1:2, pour the mixed powder into a mortar and grind thoroughly for 30 minutes to ensure uniform mixing. Place the uniformly ground powder into an alumina crucible, set the muffle furnace temperature to 1200℃ at a rate of 5℃ / min, and maintain the temperature in the furnace for 18 hours. After cooling to room temperature, remove the sample and ultrasonically clean it with deionized water until the supernatant is clear. Place the ultrasonically cleaned sample in a drying oven and dry it at 60℃. After drying, LLZTO particles with good morphology are obtained, and the volume average particle size Dv50 is measured to be 47μm.
[0085] Example 5
[0086] The preparation of LLZTO particles includes the following steps:
[0087] Weigh LLZTO pre-calcined powder and Li2CO3 + LiNO3 (mass ratio 1:1) at a ratio of 1:4. Pour the mixture into a mortar and grind thoroughly for 30 minutes to ensure uniform mixing. Place the uniformly ground powder into an alumina crucible and set the muffle furnace temperature to 1200℃ at a rate of 5℃ / min. Maintain this temperature in the furnace for 12 hours. After cooling to room temperature, remove the sample and ultrasonically clean it with deionized water until the supernatant is clear. Place the ultrasonically cleaned sample in a drying oven and dry it at 60℃. After drying, LLZTO particles with good morphology are obtained, and their volume average particle size (Dv50) is measured to be 15 μm.
[0088] Example 6
[0089] The preparation of LLZTO particles includes the following steps:
[0090] Weigh LLZTO pre-calcined powder and Li2CO3 + Li2O (mass ratio 1:1) at a ratio of 1:2. Pour the mixed powder into a mortar and grind thoroughly for 30 minutes to ensure uniform mixing. Place the uniformly ground powder into an alumina crucible and set the muffle furnace temperature to 1200℃ at a rate of 5℃ / min. Maintain the temperature in the furnace for 12 hours. After cooling to room temperature, remove the sample and ultrasonically clean it with deionized water until the supernatant is clear. Place the ultrasonically cleaned sample in a drying oven and dry it at 60℃. After drying, LLZTO particles with good morphology are obtained, and the volume average particle size Dv50 is measured to be 17μm.
[0091] As shown in Examples 1-6, by controlling the appropriate mass ratio of pre-fired powder and lithium-containing molten compound, the type of lithium-containing molten compound, and the sintering holding time, LLZTO particles with good morphology and different particle sizes can be obtained. Moreover, within a certain range, the holding time is positively correlated with the particle size Dv50, indicating that when sintering LLZTO ceramic bodies using the molten salt method, the holding time has strong controllability over the particle size.
[0092] Example 7-a
[0093] The only difference from Example 1 is that the mass ratio of LLZTO pre-calcined powder to Li2CO3 is 1:3. The resulting LLZTO particles have better morphology, and the volume average particle size Dv50 is 19 μm. The resulting product particles have better morphology and are evenly distributed.
[0094] Example 7-b
[0095] The only difference from Example 1 is that the mass ratio of LLZTO pre-calcined powder to Li2CO3 is 1:2, resulting in better LLZTO particle morphology. The volume average particle size Dv50 was measured to be 20 μm, and the particle size distribution was relatively wide.
[0096] Example 8-a
[0097] The only difference from Example 1 is that the mass ratio of LLZTO pre-calcined powder to Li2CO3 is 1:5. The resulting LLZTO particles have better morphology, and the volume average particle size Dv50 is 18 μm. The product particles have good morphology and are evenly distributed.
[0098] Example 8-b
[0099] The only difference from Example 1 is that the mass ratio of LLZTO pre-calcined powder to Li2CO3 is 1:6, resulting in better LLZTO particle morphology. The volume average particle size Dv50 was measured to be 22 μm, and the particle size distribution was relatively wide.
[0100] Example 9
[0101] The preparation of LLZTO particles includes the following steps:
[0102] The only difference from Example 1 is that the mass ratio of LLZTO pre-calcined powder to Li2CO3 is 1:10. The resulting LLZTO particles have poor sphericity, and their volume average particle size Dv50 is 100 μm, indicating uneven particle size distribution.
[0103] A comparison of Examples 1 with Examples 2-8 shows that the type of lithium-containing molten compound, the ratio of LLZTO pre-calcined powder to lithium-containing molten compound, and the calcination time are related to the sphericity and particle size of the sintered LLZTO particles. By selecting a suitable lithium-containing molten compound, adjusting the ratio of LLZTO pre-calcined powder to lithium-containing molten compound to, for example, 1:1 to 6, and using a suitable calcination time, LLZTO particles with good sphericity, suitable and controllable particle size can be obtained. A comparison of Examples 1 with Examples 7 (including 7-a and 7-b) and Examples 8 (including 8-a and 8-b) shows that when the mass ratio of LLZTO pre-calcined powder to Li2CO3 is not in the range of 1:3 to 5, the effect on morphology and Dv50 is small, but the effect on particle size distribution is more obvious. Therefore, further adjusting the mass ratio of LLZTO pre-calcined powder to lithium-containing molten compound to 1:3 to 5 can improve the particle size distribution and improve uniformity.
[0104] Example 10
[0105] The only difference from Example 1 is that the lithium-containing molten compound is LiCl, and the resulting LLZTO particles have better morphology, with a volume average particle size Dv50 of 22 μm and a wider particle size distribution.
[0106] A comparison between Examples 1 and 10 shows that when the lithium-containing molten compound is LiCl, the particle size is larger, and the grain distribution is not as uniform as that of Li₂CO₃ molten salt. This may be because Li₂CO₃ decomposes into carbon dioxide at high temperatures, and the carbon dioxide gas can prevent LLZTO grains from agglomerating at high temperatures, resulting in particles with uniform particle size distribution and smaller particle size. When using lithium-based ceramic particles as a solid electrolyte for electrolysis, smaller particle size can significantly improve electrolysis performance and extend the lifespan of the solid electrolyte, while larger particle size results in greater porosity, affecting electrolysis performance.
[0107] Example 11
[0108] The only difference from Example 1 is that the holding time for sintering is 60h. The resulting LLZTO particles have poor sphericity, severe particle agglomeration, and a volume average particle size (Dv50) of 200μm, indicating uneven particle size distribution.
[0109] As can be seen from Examples 11 and 1, the sintering holding time of LLZTO is related to the sphericity and particle size of the sintered LLZTO particles. The sintering holding time may cause severe particle agglomeration, affecting its morphology and particle size. By adjusting the holding time of LLZTO to 12-48h, LLZTO particles with good sphericity, suitable particle size and controllable particle size can be obtained.
[0110]
[0111]
[0112] In this application, by adjusting the type of lithium-containing molten compound and the mass ratio of lithium-based ceramic pre-fired powder to lithium-containing molten compound, lithium-based ceramic particles with good particle size (no adhesion or agglomeration), small particle size and uniform particle distribution can be obtained.
[0113] The above description is merely a preferred embodiment of this application and is not intended to limit this application. Any modifications, equivalent substitutions, and improvements made within the principles of this application should be included within the protection scope of this application.
Claims
1. A method for preparing lithium-based ceramic particles using a lithium-containing molten compound, characterized in that, Includes the following steps: Step S1: Provide raw material powder according to the stoichiometric ratio of lithium-based ceramics, and obtain lithium-based ceramic pre-fired powder after pre-firing; Step S2: The lithium-based ceramic pre-sintered powder is mixed with a lithium-containing molten compound and then sintered. The lithium-containing molten compound is in a molten state, and the lithium-based ceramic pre-sintered powder is sintered in this environment to obtain a sintered product. Step S3: After cooling the sintered product, wash it with a solvent to dissolve and remove the lithium-containing molten compound in the sintered product, so as to obtain cubic lithium-based ceramic particles. In step S2, the mass ratio of the lithium-based ceramic pre-calcined powder to the lithium-containing molten compound is 1:3~5; The sintering time is 12-14h, during which the volume average particle size Dv50 of the lithium-based ceramic particles obtained is 10-22μm. The sintering time is 14-16h, during which the volume average particle size Dv50 of the lithium-based ceramic particles obtained is 18-42μm. The sintering time is 16-20h, during which the volume average particle size Dv50 of the lithium-based ceramic particles obtained is 38-62μm. The sintering time is 20-24h, during which the volume average particle size Dv50 of the lithium-based ceramic particles obtained is 58-82μm. The sintering time is 24~48h, during which the volume average particle size Dv50 of the lithium-based ceramic particles is 78~110μm. The lithium-based ceramic is the substance shown in Formula 1; Li 7-x La₃Zr 2-x Ta x O 12 Formula 1; The range of x is: 0 < x ≤ 1.0; The lithium-containing molten compound is lithium carbonate.
2. The method according to claim 1, characterized in that, In step S1, the pre-firing conditions include: pre-firing at 800~1000℃ for 10~24h.
3. The method according to claim 1, characterized in that, In step S1, the raw material powder includes a lithium source, the mass of lithium element in the lithium source is denoted as m, and the theoretical amount of lithium element used is denoted as m0, satisfying 1.1×m0≤m≤1.2×m0.
4. A lithium-based ceramic particle, characterized in that, Prepared according to the method of any one of claims 1 to 3.
5. The lithium-based ceramic particles according to claim 4, characterized in that, The volume average particle size Dv50 of the lithium-based ceramic particles is 10~22μm; Alternatively, the volume average particle size Dv50 of the lithium-based ceramic particles is 18~42μm; Alternatively, the volume average particle size Dv50 of the lithium-based ceramic particles is 38~62μm; Alternatively, the volume average particle size Dv50 of the lithium-based ceramic particles is 58~82μm; Alternatively, the volume average particle size Dv50 of the lithium-based ceramic particles is 78~110μm.
Citation Information
Patent Citations
Lithium-based ceramic material and preparation method thereof
CN119430933A